Sprint mechanical properties of female and different aged male top-level German soccer players - Baumgart, C.; Freiwald, J.; Hoppe, M. W. (Sports, 2018)
This study compared the sprint mechanical properties of female and different aged male top-level soccer players. A total of 14 adult females (FEM) and 115 different aged male field players, competing at German top levels, participated in this study. The males belonged to teams of under 12, 13, 14, 15, 17, 19, and 23 years (U 12-23) and professionals (PRO). All players were tested for a 30 m linear sprint. From timing gate derived sprint times, force-velocity and power-velocity relationships, as well as theoretical maximum running velocity, force, and power data were computed by an inverse dynamic approach applied to the center of mass. The approach was optimized for taking the starting time into account, which is a progress in the present research field, when aiming to compute sprint mechanical properties by different methodological approaches under field conditions. Sprint mechanical properties of FEM were lower than those of PRO. Compared to other age groups, sprint mechanical properties of FEM were similar to those of U 14 and U 15. An increase in sprint mechanical properties was found from U 12 to U 17. The study shows that sprint mechanical properties differ according to gender and age in top-level soccer players